Analysis of Multiplicity of Hypoxia-Inducible Factors in the Evolution of Triplophysa Fish (Osteichthyes: Nemacheilinae) Reveals Hypoxic Environments Adaptation to Tibetan Plateau - Chen, Juan; Shen, Yanjun; Wang, Jing; Ouyang, Gang; Kang, Jingliang; Lv, Wenqi; Yang, Liandong; He, Shunping (Frontiers in Genetics, 2020)
HIF (Hypoxia-inducible factor) gene family members function as master regulators of cellular and systemic oxygen homeostasis during changes in oxygen availability. Qinghai-Tibet Plateau is a natural laboratory for for long-term hypoxia and cold adaptation. In this context, T. scleroptera that is restricted to > 3500 m high-altitude freshwater rivers was selected as the model to compare with a representative species from the plain, P. dabryanus. We cloned different HIF-α and carried out a phylogenetic analysis from invertebrates to vertebrates for identifying HIF-α genes and analyzing their evolutionary history. Intriguingly, the HIF-α has undergone gene duplications might be due to whole-genome duplication (WGD) events during evolution. PAML analysis indicated that HIF-1αA was subjected to positive selection acted on specific sites in Triplophysa lineages. To investigate the relationship between hypoxia adaptation and the regulation of HIF-α stability by pVHL in plateau and plain fish, a series of experiments were carried out. Comparison the luciferase transcriptional activity and protein levels of HIF-αs and the differing interactions of HIF-αs with pVHL, show clear differences between plateau and plain fish. T. scleroptera pVHL could enhance HIF-α transcriptional activity under hypoxia, and functional validation through pVHL protein mutagenesis showed that these mutations increased the stability of HIF-α and its hetero dimerization affinity to ARNT. Our research shows that missense mutations of pVHL induced evolutionary molecular adaptation in Triplophysa fishes living in high altitude hypoxic environments.